Perbandingan Perlindungan Data Pribadi Indonesia dan Malaysia - Rizal, Muhammad Saiful (Jurnal Cakrawala Hukum, 2019)
The vibrant development of information technology in the business world eliminates the barriers to one’s privacy that must be protected. Private data can be accessed by the private sector until it is traded as a field for profit. This results in legal uncertainty to the public regarding the legal protection of personal data managed by the government. This study aims to determine the comparison of personal data protection between Indonesia and Malaysia. This research is a normative legal research, with a legislative approach and a comparative approach. The results of this study are the need for regulations governing the protection of personal data in Indonesia as the Personal Data Protection Act in Malaysia which regulates the choices, goals and limitations in using personal data of the public so that it will avoid abuse or violate the user’s privacy rights. And the use of personal data between countries that already have personal data protection laws. How to cite item:Â Rizal, M. (2019). Perbandingan Perlindungan Data Pribadi Indonesia dan Malaysia.Â Jurnal Cakrawala Hukum, 10(2), 218-227. doi:https://doi.org/10.26905/idjch.v10i2.3349